Multimodal argumentation: association of words and images in the construction of the argumentative dimension of discourse - Marchon, Amanda Heiderich; Silva, Welton Pereira e; Garcia, Carlos Eduardo Nunes (Matraga - Revista do Programa de Pós-Graduação em Letras da UERJ, 2023)
Considering that discourse emerges from the multisemiotic complexity that characterizes language and, for this reason, involves different dimensions in the study of discourse materialized in texts, in this article we (re) formulated some reflections on the association between word and image as a strategy of argumentation. We assume that from the complete association between verbal and nonverbal elements, where one seems to replace the other because they have an equivalent informativeness, to the complete dissociation between these elements, where the word seems to negate the image and vice versa, there is a spectrum of association possibilities aimed at reasoning through the relationship between different modalities. To illustrate these considerations, the corpus analyzed in this article consists of seven journalistic texts of an informative nature published in the social media of media entities and on their websites. The adopted theoretical framework is mainly based on the semiolinguistic discourse theory (CHARAUDEAU, 2005; 2007; 2008), associated with the proposal of the analysis of multisemiotic texts by Kress and van Leewen (2006), as well as on previous studies in which we take as a starting point the methodological analysis of multimodal argumentation (MARCHON e GARCIA, 2020; SILVA e MARCHON, 2021). The results of the analysis point to the possibility of understanding multimodal argumentation arranged in a continuum, which can be applied to other research involving different discourse genres. ———————————————————————————————————— ARGUMENTAÇÃO MULTIMODAL: ASSOCIAÇÃO DE PALAVRAS E IMAGENS NA CONSTRUÇÃO DA DIMENSÃO ARGUMENTATIVA DO DISCURSO Considerando que o discurso emerge da complexidade multissemiótica que caracteriza a linguagem e, por essa razão, engloba diferentes dimensões na investigação de discursos materializados em textos, neste artigo, (re)formulamos algumas considerações no que concerne à associação entre palavra e imagem como estratégia de argumentação. Entendemos que, da associação completa entre elementos verbais e elemen- tos não verbais, em que um parece substituir o outro por apresentarem informatividade equivalente, até a dissociação completa entre esses elementos, em que a palavra parece negar a imagem e vice-versa, há um espectro de possibilidades associativas que visam à argumentação por meio da relação entre moda- lidades diferentes. A fim de ilustramos essas considerações, o corpus analisado neste artigo é composto por sete textos jornalísticos de caráter informativo, publicados nas redes sociais das instâncias midiáticas e em seus sites. O referencial teórico adotado ancora-se, principalmente, na Teoria Semiolinguística do Discurso (CHARAUDEAU, 2005; 2007; 2008) associada à proposta de análise de textos multissemióticos de Kress e van Leewen (2006), bem como em trabalhos anteriores em que tomamos como ponto de partida a proposta de análise metodológica da argumentação multimodal (SILVA; MARCHON, 2021; MARCHON; GARCIA, 2020). Os resultados da análise apontam para a possibilidade de compreensão da argumentação multimodal disposta em um continuum, o que pode ser aplicado a outras pesquisas com gêneros discur- sivos distintos.